2007
DOI: 10.1093/ps/86.3.525
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Bioefficacy of Lysine from l-Lysine Hydrochloride or l-Lysine Sulfate in Basal Diets Containing Graded Levels of Canola Meal for Female Broiler Chickens

Abstract: A broiler growth assay was conducted to compare the efficacy of l-lysine HCl and l-lysine sulfate at a graded addition of canola meal (CM). A total of 1,440 1-d-old female Hubbard broiler chicks were allotted randomly to 6 dietary treatments each in 4 replicates of 60 birds per pen. The 2 lysine sources (l-lysine HCl and l-lysine sulfate) and the 3 CM levels (10, 15, and 20%) were used in 2 x 3 factorial arrangement in isonitrogenous (19% CP) and equicaloric (2,700 kcal of ME/kg) diets containing 0.96% digesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
32
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 18 publications
6
32
3
Order By: Relevance
“…In contrast to present results, Ahmad et al (2007) reported that CM could be used at up to 20% of diets fed for 1 to 28 d without any adverse effects of broiler performance. The difference between results from the current study and those of Ahmad et al (2007) could partly be attributed to difference diet ingredients and composition of gut microorganism.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to present results, Ahmad et al (2007) reported that CM could be used at up to 20% of diets fed for 1 to 28 d without any adverse effects of broiler performance. The difference between results from the current study and those of Ahmad et al (2007) could partly be attributed to difference diet ingredients and composition of gut microorganism.…”
Section: Discussioncontrasting
confidence: 99%
“…The difference between results from the current study and those of Ahmad et al (2007) could partly be attributed to difference diet ingredients and composition of gut microorganism. Roland et al (1996) concluded that severity of toxicity of dietary GLS are partly dependent on the composition of the diets in which the CM is included.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Secondary plant compounds such as glucosinolates, erucic acid, phytic acid, non-starch polysaccharides (NSP), and high fibre content limit the value of canola as a major protein source in quail feed formulation. Several scholars have reported that canola is a potential protein source, but inclusion levels greater than 250 g/kg can cause detrimental effects and reduce performance in birds (Naseem et al, 2006;Ahmad et al, 2007;Min et al, 2011). A recent report by indicated that CM could be used to replace 12.5% soybean in female Japanese quail diets without compromising growth performance, health, and quality of meat.…”
Section: Introductionmentioning
confidence: 99%
“…Although the canola meal has protein content ranging from 34 to 38%, it has an amino acid profile similar to that of soybean meal. Studies on canola meal between 150 and 200 g kg -1 in the diet for broilers reported no adverse effects on the performance (Ahmad, Mirza, & Ahmad, 2007). The replacement of soybean meal with canola meal could reduce the cost of animal feed for the farmer, if there is no impact on the performance and physical characteristics of meat.…”
Section: Introductionmentioning
confidence: 99%